PRELIMINARY INVESTIGATION OF RELIGIOSITY AND ACADEMICIAN WELL-BEING: A PILOT STUDY IN A MALAYSIAN PUBLIC HIGHER EDUCATION - Siti Rosnita Sakarji; Abdul Kadir Othman; Khalijah Mohd Nor; Mutiiah Mohamad; Nur Athirah Abd Rahim (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study in general examined the influence of religiosity in improving academicians’ mental health within the context of the Job-Demand Resource (JD-R) model. The JD-R model has been utilised to comprehend how job demands and resources affect workers’ performance and well-being. Religiosity, often overlooked as a psychological resource, can play a significant role in mitigating the negative effects of job demands and enhancing employee mental health. Religiosity has increasingly gained attention as a potential contributor to improving employee mental health. This study also examines the literature and research findings that suggest a significant link between religiosity and mental health outcomes. To promote a comprehensive strategy for improving mental health in the workplace, it is important to respect employees varied religious perspectives and the necessity of inclusive workplace policies that permit employees to express their religiosity in a way that is consistent with their beliefs. Specifically, this pilot study aims to develop and test an instrument measuring variables related to religiosity and academician mental health at a public higher education institution in Malaysia. Quantitative data were collected using a questionnaire that was distributed to 100 academicians. The results demonstrate that all the measures exhibited a high level of dependability, with coefficients ranging from 0.863 to 0.918, as determined by Cronbach’s alpha coefficient test. Notably, every single one of these coefficients was higher than the criterion of 0.70. Future researchers can adopt and adapt the tested and validated instrument to their contextual studies.